Suicide in adults released from prison in Queensland, Australia: a cohort study. Issue 10 (9th July 2014) - Spittal, Matthew J; Forsyth, Simon; Pirkis, Jane; Alati, Rosa; Kinner, Stuart A
Abstract : Background: Previous research has demonstrated elevated mortality following release from prison. We contrasted the risk of opioid overdose death with the risk of suicide in a cohort of adults released from prison in Queensland, Australia over a 14-year-period. We examine risk factors for suicide in the cohort, and make comparisons with the general population. Method: We constructed a retrospective cohort of all adults released from prison between 1994 and 2007 and linked this to the National Death Index for deaths up to 31 December 2007. Results: We identified 41 970 individuals released from prison. Of the 2158 deaths in the community, 371 were suicides (crude mortality rate (CMR) 13.7/10 000 person-years) and 396 were due to drug-related causes (CMR 14.6/10 000 person-years). We observed a spike in drug-related deaths in the first 2 weeks after release from prison but no such pattern was observed for suicide. Being married (HR 0.40) and number of prior imprisonments (HR 3.1 for ≥5 prior incarcerations compared with none) independently predicted suicide. Age, sex, Indigenous status, length of incarceration and offence history were not associated with suicide. The standardised mortality ratios indicated that released women were 14.2 times and released men 4.8 times more likely to die from suicide than would be expected in the population. Conclusions: This study demonstrates that the rate of suicide in adults released from prison is similar to the rate of drug-related deaths. Strategies that provide support to vulnerable people after release may reduce suicide in this population.